GE_GERICHTE C/13262/2015 vom 31. August 2017 - GE Cour de justice (2017)
REMISE CONVENTIONNELLE DE DETTE ; DÉLAI D'EXAMEN ET DE RÉFLEXION ; INTERPRÉTATION(SENS GÉNÉRAL) | CO.341; CO.336ss; CO.337; CO.3